2011
DOI: 10.3390/ijerph8020374
|View full text |Cite
|
Sign up to set email alerts
|

Field-Scale Spatial Variation of Saline-Sodic Soil and Its Relation with Environmental Factors in Western Songnen Plain of China

Abstract: The objectives of this study were to investigate the degree of spatial variability and variance structure of salinization parameters using classical and geostatistical method in Songnen Plain of China, which is one of largest saline-sodic areas in the World, and to analyze the relationship between salinization parameters, including soil salinity content (SC), electrical conductivity (EC), sodium adsorption ratio (SAR), and pH, and seven environmental factors by Pearson and stepwise regression analysis. The env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 20 publications
1
23
0
3
Order By: Relevance
“…Soil pH did not however, show any significant directional variation (anisotropic behavior) in vertisols of the study area at the scale measured. This result agrees with the findings of Yang et al [12] who showed that soil heterogeneity and spatial dependence of pH at microscale exist and vary with sampling site and scale, while Khan et al [13] and Ayoubi [14] pH reported low variations in pH in a field under uniform management in the temperate region. Fig.…”
Section: 11soil Phsupporting
confidence: 92%
See 2 more Smart Citations
“…Soil pH did not however, show any significant directional variation (anisotropic behavior) in vertisols of the study area at the scale measured. This result agrees with the findings of Yang et al [12] who showed that soil heterogeneity and spatial dependence of pH at microscale exist and vary with sampling site and scale, while Khan et al [13] and Ayoubi [14] pH reported low variations in pH in a field under uniform management in the temperate region. Fig.…”
Section: 11soil Phsupporting
confidence: 92%
“…Moreover, these studies do not consider variability on smaller farms that fall within field scale of a hectare or less, typically found in Nigeria. The fact remains that the shorter the sampling range the less the variation [12][13]14][2] [15]. But the effect of this less variation could still be significant on crops of a given site given the prevailing conditions; thus the need to measure the small variations in soil properties distributions.…”
Section: Imentioning
confidence: 99%
See 1 more Smart Citation
“…Depressions were covered by Phragmitesaustralis due to seasonal waterlogging. Roots are intricately crossed and extended to 60 cm in the soil profile [33]. The advanced root system of Phragmitesaustralis can create more active soil pores, which in turn will increase the infiltration capacity [34].…”
Section: Key Factors Affecting Spatial Distribution Of Surface Soil Smentioning
confidence: 99%
“…Corwin and Lesch (2005) also reported moderate to high variability in SAR in saline-sodic soil. However, Yang et al, (2011) …”
Section: Sodium Adsorption Ratio (Sar)mentioning
confidence: 99%